PENGARUH KEWIRAUSAHAAN, PELATIHAN USAHA DAN JARINGAN KERJASAMA KELEMBAGAAN TERHADAP KINERJA UNIT USAHA PADA SENTRA IKM TELUR ASIN (STUDI KASUS PADA SENTRA IKM TELUR ASIN DI DESA LIMBANGAN WETAN KECAMATAN BREBES, KABUPATEN BREBES) - Kamala Dinni Sofiyah; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2016)
Development of small-scale industries such as household and industrial industries large scale has been carried out in various regions across Indonesia, including Brebes. SME development is not just a problem of operational assistance or facilities. The development must be strategic and have a long term impact. In particular, the study discusses the salted egg IKM Brebes Limbangan Wetan village. The purpose of this study was to determine the effect of entrepreneurship, business training and networking of institutional cooperation to company performance. This type of research is explanatory research. Mechanical sampling using non-probability sampling. The number of samples of 51 respondents, using a sampling technique that is saturated with a certain considerations. This study uses qualitative and quantitative analysis techniques. Quantitative analysis using validity, reliability test, correlation coefficient, simple regression analysis, coefficient of determination, significance test (t test) using SPSS 23.0. The results of this study indicate that the company's performance can be explained by the entrepreneurship of 25.1% with a result of 4,525 t count> t table 2.009. The company's performance can be explained by the training effort of 25.1% with the results for 3434 t count> t table 2.009. The company's performance can be explained by a network of institutional cooperation with results of 20.6% amounting to 3.561 t count> t table 2.009. Suggestions in this research that employers should always promote creativity and innovation, it still needs to be improved information on training events held and an increase in the attention of the parties and agencies involved in the provision of funding and capital support.